Student Views on the Effectiveness of Learning Management System Edlink - Rezki Rahmadona; Khairunnisya; Sri Wahyuni (International Journal of Pedagogy, 2024)
Sevima Edlink is an educational platform based on Learning Management System that is useful for students to be more motivated in learning. Based on this, the effectiveness of using Edlink for students is included in the very good category. The conclusion of this study obtained the effectiveness of the Edlink learning management system learning media for students, because Edlink can make learning more effective and efficient which is assisted by its easy-to-understand and interesting features so that it is easy to use. So that students' views on the use of Edlink both as an interactive learning and assessment medium. This research is limited to the use of Edlink as a distance learning medium. So, this research can also be expanded again by developing research objects in offline learning to see whether Edlink learning media is effective when used in offline learning